What is 40+40×0+1=?
and can the answer be squared

Answers

Answer 1
Answer: order of opertations
PEMDAS
parenthasees
exponnents
multipication or division
additon or subtraction

first multiply since no exponents or partnehasees

40 times 0=0


now we have
40+0+1
now we add
40+0+1=41


any number can be squared


Related Questions

What is slope point form
A system of equations is shown below: 6x - 5y = 5, 3x + 5y = 4. The x-coordinate of the solution to this system of equation is what?Thank you to however can help me with this. I've been having a lot of trouble with this math concept. :)
A candy jar contains 120 pieces of candy, including 45 red candies. If the ratio of red candies to the total number of candies in the jar remains the same, how many red candies would there be in a jar containing 200 pieces of candy?
4- What are the different waysto solve a quadratic? List examples of each
There are some books on three shelves. On the bottom shelf there are half as many books as on the other two shelves. On the middle shelf there are three times less than on the other two shelves. On the top shelf there are 30 books. How many books are on all three shelves?

Write x^2 − 8x + 13 = 0 in the form (x −a. ^2 = b, where a and b are integers.

(x − 4)^2 = 3
(x − 3)^2 = 2
(x − 2)^2 = 1
(x − 1)^2 = 4

Answers

If you would like to write the equation in the above form, you can calculate this using the following steps:

x^2 - 8x + 13 = 0
(x - 4)^2 = x^2 - 8x + 16
(x - 4)^2 - 3 = 0
(x - 4)^2 = 3

The correct result would be (x - 4)^2 = 3.

12x2 – 14x - 10
Factored form

Answers

Answer:

2(2x + 1)(3x - 5)

Step-by-step explanation:

The rectangle below has an area of x ^ 2 - 16 square meters and a width of x + 4meters . What expression represents the length of the rectangle?

Answers

Answer:

length=x-4

Step-by-step explanation:

Simplify where possible 3a - 4a 6a

Answers

the answer is 5a. 3a- 4a is -1 then you add -1 and 6, and your outcome comes out to be 5a.

Pls help....................

Answers

b^2+6b=0\nb(b+6)=0\nb=0 \vee b=-6\n\n5x^2-5x=0\n5x(x-1)=0\nx=0 \vee x=1\n\n-10x+35x=0\n25x=0\nx=0\n\n2x+15x=0\n17x=0\nx=0\n\n18x^2+6x=0\n6x(3x+1)=0\nx=0 \vee x=-(1)/(3)\n\n-32x^2-24x=0\n-8x(4x+3)=0\nx=0 \vee x=-(3)/(4)

What is the rate of change from 1 to 3

Answers


The rate of change is    (amount of the change) / (time it took to change) .

Amount of the change = (3 - 1) = 2 .

Rate of change = (2) / (time it took to change from  1  to  3) .